Plasmalogens and Chronic Inflammatory Diseases - Bozelli, José Carlos; Azher, Sayed; Epand, Richard M. (Frontiers in Physiology, 2021)
It is becoming widely acknowledged that lipids play key roles in cellular function, regulating a variety of biological processes. Lately, a subclass of glycerophospholipids, namely plasmalogens, has received increased attention due to their association with several degenerative and metabolic disorders as well as aging. All these pathophysiological conditions involve chronic inflammatory processes, which have been linked with decreased levels of plasmalogens. Currently, there is a lack of full understanding of the molecular mechanisms governing the association of plasmalogens with inflammation. However, it has been shown that in inflammatory processes, plasmalogens could trigger either an anti- or pro-inflammation response. While the anti-inflammatory response seems to be linked to the entire plasmalogen molecule, its pro-inflammatory response seems to be associated with plasmalogen hydrolysis, i.e., the release of arachidonic acid, which, in turn, serves as a precursor to produce pro-inflammatory lipid mediators. Moreover, as plasmalogens comprise a large fraction of the total lipids in humans, changes in their levels have been shown to change membrane properties and, therefore, signaling pathways involved in the inflammatory cascade. Restoring plasmalogen levels by use of plasmalogen replacement therapy has been shown to be a successful anti-inflammatory strategy as well as ameliorating several pathological hallmarks of these diseases. The purpose of this review is to highlight the emerging role of plasmalogens in chronic inflammatory disorders as well as the promising role of plasmalogen replacement therapy in the treatment of these pathologies.